ADMA elevation does not exacerbate development of diabetic nephropathy in mice with streptozotocin-induced diabetes mellitus. (December 2019) - Rodionov, Roman N.; Jarzebska, Natalia; Schneider, Alfred; Rexin, Annett; Sradnick, Jan; Brilloff, Silke; Martens-Lobenhoffer, Jens; Bode-Böger, Stefanie M.; Todorov, Vladimir; Hugo, Christian; Weiss, Norbert; Hohenstein, Bernd
Abstract: Background and aims: Cardiovascular disease is nowadays the major cause of mortality and morbidity worldwide. The risk of developing cardiovascular disease is significantly increased in patients with diabetic nephropathy. It has been suggested that asymmetric dimethylarginine (ADMA), an endogenous inhibitor of NO synthases (NOS), may play an important role in the pathogenesis of diabetic nephropathy. ADMA is mainly metabolized by dimethylarginine dimethylaminohydrolase 1 (DDAH1). The goal of this study was to test the hypothesis that elevation of systemic ADMA levels by knocking out DDAH1 would exacerbate functional and structural glomerular abnormalities in a murine model of diabetic nephropathy. Methods: Streptozotocin (STZ) was used to induce diabetes in adult DDAH1 knock-out and wild type mice. Healthy mice served as controls. Mice were sacrificed after 20 weeks of diabetes. Plasma ADMA levels were assessed by isotope-dilution tandem mass spectrometry and albumin by ELISA. Kidneys were used for FACS analysis and were also stained for markers of inflammation, cell proliferation, glomerular cells and cell matrix. Results: STZ led to development of diabetes mellitus in all injected animals. Deficiency of DDAH1 led to a significant increase in plasma ADMA levels in healthy and diabetic mice. The diabetic state itself did not influence systemic ADMA levels. Diabetic mice of both genotypes developed albuminuria and had increased glomerulosclerosis index. There were no changes in desmin expression, glomerular cell proliferation rate, matrix expansion and expression of Mac-2 antigen in the diabetic mice of both genotypes as compared to the healthy ones. Conclusions: In summary, STZ-induced diabetes led to the development of early features of diabetic nephropathy. Deficiency of DDAH1 and subsequent increase in systemic ADMA levels did not exacerbate these changes, indicating that ADMA is not the major mediator of diabetic nephropathy in this experiment model.